Aspek Reproduksi Ikan Lemuru (Sardinella lemuru) yang Didaratkan di Pelabuhan Perikanan Nusantara (PPN) Pengambengan, Bali - Ribka Evanzelina Laia; I Wayan Restu; Made Ayu Pratiwi (Current Trends in Aquatic Science, 2021)
Sardinella (Sardinella lemuru) is a type of small pelagic fish which very important and economic value in Pengambengan Nusantara Fishing Port (NFP). Sardinella resources are stated to be in overfishing were marked by the catch that is getting smaller and the production has decreased every year. The situation of Sardinella resources in Bali Strait, especially in Pengambengan NFP must be maintained by managing, then stocks of Sardinella can be utilized sustainably. This research aims to provide an overview of conditions and threats to Sardinella around Pengambengan NFP as one of the largest fishing ports in Bali Strait includes Sardinella fisheries production in Pengambengan NFP, sex ratio, gonad maturity level, gonad maturity index, conditions factor, so Sardinella resources can be created sustainable. This research uses a simple random sampling method, by taking fish randomly from traders who contain various lengths and weights of Lemuru in Pengambengan NFP. Lemuru production from 2009-2018 in PPN Pengambengan has increased and decreased, this is due to several factors such as environmental changes and fishing activities by fishermen. The sex ratio of Sardinella landed in Pengambengan NFP has a ratio of 0.8: 1. Gonad Maturity Level obtained in TKG I and TKG II so the Gonad Maturity Index found was around 0.0291-0.2188. The range of condition factors from 0.9-1.4, it means Sardinella in the plump category.Sardinella lemuru; PPN Pengambengan; Reproduction